(untitled) (Progressive Agriculture, 2013)
The experiment was conducted at the Bangladesh Institute of Nuclear Agriculture (BINA) sub-staion, Tajhat, Ranpure, using potato-Boro-T. aman rice cropping pattern with an objective to evaluate the direct and residual effects of sulphur and zinc on the growth, yield and nutrient uptake by the crops. The surface soil was sandy loam texture, pH 6.3, organic matter 1.24%, available sulphur 6.62 ppm and available zinc 0.45 ppm. The experiment comprised of eight treatments for potato S15Zn2 (T2, T4 and T8, S8Zn1 (T5 and T6)and S0Zn0 (T1, T3 and T7), for boro rice S20Zn4 (T3, T5, T6 and T7) and S0Zn0 (T1, T3, T4 and T6). The experiment was laid out in a randomized complete block design with three replications. Average tuber yield of potato (var. cardinal) varied from 28.29 to 32.86 t ha-1 with the highest yield in S15Zn2 treatment (100% recommended dose) and the lowest was in the S0Zn0 treatment (control). In the second crop (Boro rice), growth and yield attributes, grain and straw yields responded significantly to S and Zn applied either in the first crop or in both crops. The average grain yield varied from 3.51 to 5.27 t ha-1 over the treatments. In the third crop (T. aman rice), the grain and straw yields responded significantly to S and Zn applied either in the first and second crop or in the third crops. The grain yield of T. aman rice varied from 2.96 to 4.46 t ha-1 over the treatments. The growth and yield contributing characters were also significantly influenced by the treatment. There was a significant direct and residual effect of the treatments on S and Zn uptake by the crops. DOI: http://dx.doi.org/10.3329/pa.v19i1.16987 Progress. Agric. 19(1): 33 - 38, 2008